Grammar teaching at pre-service training program in Kampung Inggris (a case study on mastering system program) - Fitri Rakhmawati; Widya Nirmalawati (Politeknik Negeri Bali, 2017)
Kampung Inggris is a very popular English learning area as there are many English courses with various programs are offered. Mastering System is a pre-service training program at one of the leading courses in Kampung Inggris. They are devoted exclusively to graduates or instructors interested in teaching in formal or non-formal schools. The purpose of this research is to reveal the process of teaching Grammar on Mastering System program. This research is a qualitative research using case study design. Data was collected through interviews, observation, and document analysis. There were a total of 3 teachers and 5 students interviewed. Observations were made to find out how teachers and students perform the learning and teaching process in the Grammar class as well as outside the classroom. Documents used in the form of field notes, transcripts recording interviews, brochures, schedules and subject matter. Document analysis was done by organizing data, coding and reducing, and representing. Based on data analysis, it can be concluded that Grammar teaching process in MS program is carried out in two activities, namely Grammar class and Study Club. In classroom learning, instructors apply the PBL (Problem-Based Learning) method. In Study Club activities, teaching is done in tutorial with the delivery of material using CTL (Communicative Language Teaching). The purpose of Grammar teaching is for MS students to be able to improve Grammar understanding through the cases found in the giving of tutorials to juniors. In addition, MS students can practice firsthand how Grammar's teaching process before going to school. From the results of interviews and observations obtained the conclusion that the involvement of students actively in learning Grammar able to create effective learning.